2017
DOI: 10.1007/s41066-017-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Measures of the Shapley index for learning lower complexity fuzzy integrals

Abstract: The fuzzy integral (FI) is used frequently as a parametric nonlinear aggregation operator for data or information fusion. To date, numerous data-driven algorithms have been put forth to learn the FI for tasks like signal and image processing, multi-criteria decision making, logistic regression and minimization of the sum of squared error (SEE) criteria in decision-level fusion. However, existing work has focused on learning the densities (worth of just the individual inputs in the underlying fuzzy measure (FM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…To answer this question, a method based on the computation of the Shapley Index [31] is proposed in this study. The Shapley index is generally used to assess the quality of the feature discrimination for the resulting models.…”
Section: Probabilistic and Possibilistic Modeling Of The Information mentioning
confidence: 99%
“…To answer this question, a method based on the computation of the Shapley Index [31] is proposed in this study. The Shapley index is generally used to assess the quality of the feature discrimination for the resulting models.…”
Section: Probabilistic and Possibilistic Modeling Of The Information mentioning
confidence: 99%
“…Another approach to obtain ensemble classification is the use of the Fuzzy Integral (FI) aggregation defined with respect to a Fuzzy Measure (FM) [4][5][6][7][8]. The FI is a non-linear aggregation operator to fuse weighted information from multiple sources, where the weights are captured by a FM.…”
Section: Introductionmentioning
confidence: 99%
“…These works further concluded that DeFIMKL was the best among decision level fusion based FI-FM based ensemble classifiers and thus it has been selected in the work as representative of the FI-FM based ensemble classifier family. However, no in-depth comparison of the FI-FM based ensemble classifier with other ensemble methods have been found in the literature [4][5][6][7][8][9] (discussed in detail in section 2.3). Thus, the motivation of this study is to determine the performance of FM-FI based ensemble methods for the purpose of ensemble classification.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the inherent complexity and uncertainty of the decision situation or the existence of multiple and conflicting objectives, decision-making problems are complex and difficult; particularly in the era of big data, decision making becomes more complicated because the huge amounts of decision information and alternatives are continuously growing. Many new decision-making methods, such as granular computing techniques [1,[6][7][8][9][10], have been proposed for expressing complex or uncertain information in decision-making processes and solving decision-making problems [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%